Chapter 9 Becoming Common - Ecological Resistance, Refusal, Reparation - Petersmann, Marie (Taylor & Francis, 2024)
This chapter thinks through international law and posthuman theory by way of an example of 'posthumanist commoning'. It explores the posthumanist and the commoning dimensions of the legal and political collective actions at hand. It does so by telling the story of the 'insurgent lake' of Rome - the 'lago bullicante'. Bullicante is an archaic Italian term that signifies both 'to boil' (bollire) and 'to get agitated' (agitarsi). The 'lake that boils and gets agitated' refers to the artificial/natural lake that was accidentally created in 1992, when an underground parking lot was illegally constructed and inadvertently hit an aquifer, thereby flooding the construction site and nearby area, creating a one-hectare large lake in the heart of the city. With the lake, an insurgent political subjectivity emerged to resist and care for its preservation. Both the subjectivity and the struggle are articulated and practiced in non-liberal, non-individualistic, and in-human (or more and less than 'human') terms, thereby giving rise to a distinctive mode of 'becoming common'. Drawing on the lago bullicante, I argue that this mode of 'posthumanist commoning' enacts particular practices of ecological resistance, refusal, and reparation. The transversal alliances forged within networks of transnational resisting collectives help exploring how posthuman theory can inform international law. It does so by availing methods of reconfiguring the categories of the human, the land, and its living ecology, while also revealing critical blind-spots and methodological/conceptual limitations of both posthuman theory and international law.